Դեյվիդ Աթկինսոնի զեկույցը Եվրոպայի Խորհրդի խորհրդարանական վեհաժողովում (2005 թ.) - Քեռյան, Գարիկ (YSU Journal of International Affairs, 2015)
2002-2005, Committee for Political Affairs of the Parliamentary Assembly of the Council of Europe was discussing Nagorno-Karabakh conflict. Initially, the reporter on this issue has been appointed a member of the socialist faction Terry Davis, then a member of the Democratic faction David Atkinson. January25, 2005, after lengthy discussions PACE, adopted a resolution on Nagorno-Karabakh conflict, based on Atkinson's report /resolution No. 1416 /. Despite the fact, that this document includes some favorable points for Azerbaijan, it evidences the importance ofprotecting the separation of a particular territory from the State by democratic methods.
Keywords: PACE, Nagorno-Karabakh, determination, resolution, conflict, diplomacy, Azerbaijan, Armenia